Stress hormone norepinephrine incites resistance of oral cancer cells to chemotherapy - Tjioe, Kellen Cristine [UNESP]; Cardoso, Diovana Melo [UNESP]; Oliveira, Sandra Helena Penha de [UNESP]; Bernabé, Daniel Galera [UNESP] (Bioscientifica, 2022)
This study investigated whether norepinephrine (NE) and epinephrine (E) interfere in the response of head and neck squamous cell carcinoma (SCC) cell lines to cisplatin and explored the mechanisms of chemoresistance. Head and neck SCC-derived cell lines SCC-9, Cal27, SCC-25, and FaDu were stimulated with NE or E and treated with the inhibitory concentration of cisplatin for 24 h. As for adrenergic receptors (ADRB) inhibition, cells were treated with propranolol. The results showed that, when combined with NE, cisplatin effectiveness against SCC-9 and Cal27 but not SCC-25 and FaDu cells were notably reduced. E did not affect the response of the cells to cisplatin. Further experiments were performed with the responsive SCC-9 and SCC-25 cell lines and the hormone NE. The time course assay showed that stimulation of oral SCC cells with NE decreased the cleavage of caspase-3 and expression of multidrug resistance protein 1 (MDR-1) but only transiently affected ATP-binding cassette (ABC) subfamily G, isoform 2 protein (ABCG2) expression. The expression of cleaved caspase-3 and Bcl-2 were, respectively, decreased and increased by the combination of NE and cisplatin in SCC-9 and Cal27 cells. NE-induced resistance was reverted by previous treatment with propranolol. Expressions of ABCG2, and p-Akt but not of MDR-1, were enhanced by NE plus cisplatin when compared to cisplatin only in both cell lines. Migratory activity of oral SCC cells challenged with cisplatin was not affected by NE. These findings reveal for the first time that stress hormone NE induces resistance of oral cancer cells to cisplatin in vitro through the ADRB/Akt/ABCG2 pathway, pumping the drug out of the cell and inhibiting apoptosis.
Keywords: ABCB1; ABCG2; ADRB1; ADRB2; adrenergic; Akt; chemotherapy; cisplatin; oral squamous cell carcinoma; stress